Burden of active pulmonary tuberculosis among patients with diabetes in Dar es Salaam, Tanzania: a cross-sectional study. Issue 11 (24th November 2022) - Makuka, Gerald Jamberi; Balandya, Emmanuel; Munseri, Patricia
Abstract : Objectives: We aimed to determine the prevalence, associated factors and describe the chest radiographic findings for active pulmonary tuberculosis (TB) among patients with diabetes mellitus (DM) attending a diabetic clinic in Tanzania. Design: Cross-sectional study. Setting: A diabetic clinic at Temeke Regional Referral Hospital in Dar es salaam, Tanzania. Participants: Patients with diabetes. Main outcome measures: The prevalence and factors associated with active TB in patients with DM. Results: Among 623 patients with DM screened, 11 (1.8%); 95% CI 0.9 to 3.1, had active TB of which 6 (54.5%) were GeneXpert positive and 5 (45.5%) were diagnosed based on clinical symptoms and suggestive chest radiographs. The risk of active TB was lower in patients aged 45–64 years compared with age below 45 years (adjusted prevalence ratio (aPR) 0.39, 95% CI (0.11 to 0.42), p=0.001) and in patients with normal chest examination findings compared with patients with crackles or bronchial breathing sounds (aPR 0.02, 95% CI (0.01 to 0.15), p<0.01). The predominant chest radiographic findings were opacification 100% mainly in the upper and mid-lung zones. Conclusion: Diabetics should be screened for pulmonary TB, particularly among individuals aged 45 years and below with crackles or bronchial breathing on auscultation of the chest. High index of suspicion could help in the early detection and control of TB.